Myosin-based nucleation of actin filaments contributes to stereocilia development critical for hearing - Zane G. Moreland; Fangfang Jiang; Carlos Aguilar; Melanie Barzik; Rui Gong; Ghazaleh Behnammanesh; Jinho Park; Arik Shams; Christian Faaborg-Andersen; Jesse C. Werth; Randall Harley; Daniel C. Sutton; et al. (Nature Communications)
Abstract Assembly of actin-based stereocilia is critical for cochlear hair cells to detect sound. To tune their mechanosensivity, stereocilia form bundles composed of graded rows of ascending height, necessitating the precise control of actin polymerization. Myosin 15 (MYO15A) drives hair bundle development by delivering critical proteins to growing stereocilia that regulate actin polymerization via an unknown mechanism. Here, we show that MYO15A is itself an actin nucleation-promoting factor. Moreover, a deafness-causing mutation in the MYO15A actin-binding interface inhibits nucleation activity but still preserves some movement on filaments in vitro and partial trafficking on stereocilia in vivo. Stereocilia fail to elongate correctly in this mutant mouse, providing evidence that MYO15A-driven actin nucleation contributes to hair bundle biogenesis. Our work shows that in addition to generating force and motility, the ATPase domain of MYO15A can directly regulate actin polymerization and that disrupting this activity can promote cytoskeletal disease, such as hearing loss.